Smart specialization, public authorities, and innovation intermediaries in developing regions - Hugo Pinto; Manuel Laranja; Elvira Uyarra (Regional Sustainability, 2024)
Despite a growing body of literature on smart specialization, the role of public authorities and innovation intermediaries, particularly in developing regions, remains understudied. This research examines one of the first attempts to apply the smart specialization framework to the development of an innovation strategy outside Europe, specifically in the Pernambuco State, Brazil. We focus on two priority areas (clothing and high-tech automotive components) identified by the state government as key targets for pilot policy experimentation and use different methods, such as social network analysis and content analysis, to interview strategic innovation actors for studying the promotion of innovation and regional development in Pernambuco. Findings highlight how regional governance, collaboration, and trust are shaped by public authorities and innovation intermediaries. The study identifies three key challenges in implementing smart specialization strategy in developing regions: i.e., achieving effective decentralization, cultivating an innovation culture, and establishing participatory governance mechanisms. The public sector actors act as crucial knowledge brokers and policy intermediaries, facilitating the linkages and partnerships necessary to overcome these challenges.